Is the METS-IR Index a Potential New Biomarker for Kidney Stone Development? - Shen, Xudong; Chen, Yang; Chen, Yan; Liang, Hu; Li, Guoxiang; Hao, Zongyao (Frontiers in Endocrinology, 2022)
The purpose of this study was to examine whether the METS-IR index is associated with kidney stones in American adults. Participants from the National Health and Nutrition Examination Survey (NHANES) database from 2007–2018 were selected for logistic regression analysis, subgroup analyses, and the calculation of dose-response curves to assess the association between the METS-IR index and the incidence of kidney stones. Result: This study enrolled 30,612 adults aged > 20 years, 2901 of whom self-reported having had kidney stones in the past. And, after controlling for potential confounders, each unit increase in the METS-IR index was linked with a 1.23 percent rise in kidney stone incidence (OR = 1.0123, 95% CI: 1.0092–1.0155), with stratified analysis indicating that this was true in all subgroups. Between all groups, an elevated METS-IR index was related to kidney stone formation, and the dose-response curve revealed a positive non-linear connection between METS-IR index and kidney stone risk, with a threshold effect analysis revealing an inflection point value of 50.8314. Conclusion: A higher METS-IR index is associated with the occurrence of kidney stones, and while no causative association can be shown, this is cause for concern.